Grand Successes and Failures in IT. Public and Private Sectors IFIP WG 8.6 International Working Conference on Transfer and Diffusion of IT, TDIT 2013, Bangalore, India, June 27-29, 2013. Proceedings - Dwivedi, Yogesh K.; Henriksen, Helle Zinner; Wastell, David; De$1 (B, Rahul.s; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the IFIP WG 8.6 International Working Conference on Transfer and Diffusion of IT, TDIT 2013, held in Bangalore, India, in June 2013. The 35 revised full papers presented together with an invited paper, 12 short papers and 3 poster papers were carefully reviewed and selected from 65 submissions. The full papers are organized in the following topical sections: IS success and failure; studies of IT adoption; software development; IT in the public sector; and theory and methods.
IS success and failure -- Studies of IT adoption -- Software development -- IT in the public sector -- Theory and methods.
Keywords: Computer science; Computers and civilization; Management information systems; Computer Science; Computers and Society; Management of Computing and Information Systems; Information Systems Applications (incl. Internet).; Electronic books